Bubaline cryptosporidiosis - De Aquino, Monally Conceição Costa [UNESP]; Do Amaral, Anaiza Simão Zucatto; Inácio, Sandra Valéria [UNESP]; Da Cruz Panegossi, Mariele Fernanda [UNESP]; Fermino, Bruno Rafael; Alcindo, Jefferson Filgueira [UNESP]; Do Prado, Tales Dias; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
Cryptosporidium is an important protozoan parasite that infects a wide range of animals, including humans. The molecular characterization of isolates from different origins (animal, human and environmental) has been widely used to investigate the epidemiology of these parasites. Cryptosporidium parvum is an important agent of neonatal diarrhea in ruminants and one of the major causes of human cryptosporidiosis, this species has been detected in buffaloes in many countries. Although the significance of these animals as reservoirs is limited, several studies suggest that buffaloes may contribute to zoonotic transmission of Cryptosporidium species or genotypes.
Keywords: Cryptosporidium; Species; Water buffaloes